Learning styles and the learning process - Ovsiew, Gordon; Instructivision, Inc. (Reston, Va.: Inservice Video Network, 1991)
Looks at what learning styles are, how to use learning style teaching to enable students to learn better and faster
Camera, Andy Abbot
Presenter: Marie Carbo
Keywords: Learning, Psychology of; Learning; Cognitive styles; Teaching